Meningkatkan Hasil Belajar Siswa dengan Menggunakan Model Pembelajaran Kooperatif Tipe Group Investigation (GI) pada Pelajaran Tematik Kelas III-A SD Negeri 071060 Lasara Idanoi Kecamatan Gido Kabupaten Nias T.P. 2022/2023 - Masnidar Lombu (Departement of Mathematics Education, 2023)
This research was carried out at SD Negeri 071060 Lasara Idanoi, Gido District, Nias Regency. This type of research is Classroom Action Research (PTK) using experimental methods in learning which aims to find out the extent to which the use of experimental methods can improve student learning outcomes in thematic lessons in class III-A of state elementary school 071060 Lasara Idanoi, Gido sub-district, Nias district. The subjects of this research were Class III-A students at state elementary school 071060 Lasara Idanoi, Gido District, Nias Regency with a total of 28 students consisting of 14 men and 14 women. From the results of this research, an increase in learning outcomes was obtained after the action was implemented. The results of the research in cycle I averaged a class of 69.97. Of the remaining 28, 13 people (65%) completed it. Furthermore, in cycle II the class average increased to 78.80, of which 28 students were found to have completed (100%). Starting from the increase in classical mastery obtained by students, it can be concluded that the use of experimental methods can improve student learning outcomes.